Anti-imperialism: The Leninist Legacy and the Fate of World Revolution. Issue 3 (23rd October 2017) - Friedman, Jeremy; Rutland, Peter
Abstract : The most important of Lenin's writings was, arguably, Imperialism: the Highest Stage of Capitalism. That work shifted the focus from workers' struggles within one country to the dynamics of capitalism as a global system. The Leninist project thereby inextricably linked the causes of economic justice and national liberation, a fateful step in light of the transformation of the world wrought by decolonization. As capitalism stumbles through yet another global crisis today, what parts of Lenin's fevered vision remain relevant 100 years later?